Effect of oyster mushroom powder on total leukocyte during inflammatory and proliferative phases of the wound healing process of third-degree burns model in Wistar rat (Rattus norvegicus) - Elfiah, Ulfa; Mochammad Amrun Hidayat; Elly Nurus Sakinah; Candra Agung Wibisana; Ramadhani, Alfiyah; Apryanita, Hudayah (Published by Universitas Gadjah Mada, 2025)
Burn wounds are challenging to treat because they often heal slowly and are susceptible to complications. The inflammatory phase plays an essential role in the repair process. However, prolonged inflammation can delay tissue healing. The total leukocyte count is an important parameter to evaluate the process, as it reflects the balance between inflammation and the initiation of tissue regeneration. Oyster mushrooms (Pleurotus ostreatus) contain β-glucans and phenolic compounds with anti-inflammatory and antioxidant properties, which may help regulate leukocyte activity and promote wound healing. This study aimed to evaluate the effect of oyster mushroom powder on total leukocyte counts during burn wound healing in Rattus norvegicus. Twenty-seven healthy male rats aged 2-3 mo were randomly divided into 3 groups, with 9 rats in each group. The negative control group received aquadest, the positive control group received bovine serum albumin, and the treatment group received 10% oyster mushroom powder. All groups received identical topical wound management with 1% silver sulfadiazine ointment to prevent infection and maintain a moist wound environment during healing. Blood samples were collected on days 0, 4, 8, and 12 after burn induction, and leukocyte counts were measured. The results showed that the treatment group consistently had lower leukocyte counts compared with control groups. On day 0, the treatment group had significantly lower leukocyte levels compared with the negative control (p = 0.019). On day 8, leukocyte counts in the treatment group were also significantly lower than the positive control (p = 0.030). By day 12, all groups showed a decrease, but the treatment group demonstrated the most gradual and stable reduction over time. In conclusion, oyster mushroom powder reduces leukocyte levels and supported a more controlled inflammatory phase, allowing faster progression to proliferation and improved burn wound healing.